AB0540 Post-Thrombotic Syndrome and Venous Disease Spesific Quality of Life in Patients with Vascular Behçet's Disease. (15th July 2016) - Alibaz-Oner, F.; Aldag, B.; Aldag, M.; Unal, A.U.; Mutis, A.; Toptas, T.; Ergun, T.; Direskeneli, H.
Abstract : Background: Behçet's disease (BD) is a systemic disease characterized by oral aphthosis, genital ulcers, ocular lesions and systemic involvement including major vessels. Vascular Behçet's disease (VBD) is observed in up to 40% of BD. It is one of the major causes ofmorbidity and mortality in BD. Deep venous thrombosis (DVT) is the most common form of vascular involvement in Behcet's disease (BD). Post-thrombotic syndrome (PTS) develops in up to one-half of patients with DVT and is associated with impaired quality of life (QoL). There is no data on severity of DVT related PTS and its impact on quality of life in patients with Vascular Behçet's Disease (VBD). Objectives: We aimed to evaluate frequency of PTS and venous disease spesific QoL in VBD and to compare it with patients having DVT associated with non-Behçet's disease (NBD) causes. Methods: This study included 50 patients (Male/Female: 41/9) with VBD and 31 age and gender-matched individuals (Male/Female: 22/9), with DVT associated with non-BD causes. Villalta scale was used to assess of PTS. Venous Disability Score (VDS) and Venous Clinical Severity Score (VCSS) were used for the assessment of venous disease. Venous disease-specific QoL was measured through Venous Insufficiency Epidemiological and Economic Study Quality of Life/Symptom questionnaire (VEINES-QoL/Sym). Behçet Syndrom Activity Score (BSAS) questionnaire was used to assess disease activity. Results: We observed significantly lower risk of PTS together with significantly better VEINES-QoL, VEINES-Sym and VDS in VBD group compared to NBD group. When VBD patients with PTS were compared to patients without PTS; VEINES-QoL, VEINES-Sym VCSS were significantly worse. BSAS was also significantly higher in patients with PTS. An inverse correlation was found between VEINES-QoL and BSAS in multivariate analysis. There were no differences between anticoagulant users and non-users regarding the presence of PTS and scores of all venous assessment tools. Conclusions: We found lower PTS risk and better venous disease spesific QoL, symptom severity and venous disability scores in VBD compared to NBD group. Venous disease spesific QoL negatively correlated with disease activity. Effective control of vascular inflammation through treatment in VBD might explain lower PTS and better venous QoL outcomes in VBD patients. Our results suggest that successful control of disease activity might decrease development of PTS, improve venouse disease spesific QoL as well as preventing the relapses in VBD. Disclosure of Interest: None declared